MORFOLOGI CERITA WADU NTANDA RAHI MODEL ANALISIS VLADIMIR PROPP - Damayanti, Sri; Mahyudi, Johan; Burhanuddin, Burhanuddin (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study aims to examine the function in the story of Wadu Ntada Rahi based on the analytical model developed by Vladimir Propp. The main problem studied in this study includes the function (action) of the actor in the story. The method used is descriptive qualitative method with data collection techniques through literature study. the results of the analysis that in the story of Wadu Nttada Rahi can be found the function of crime, the function of going.